Near-Infrared Cerebral Oximetry to Predict Outcome After Pediatric Cardiac Surgery: A Prospective Observational Study*. Issue 5 (May 2018) - Flechet, Marine; Güiza, Fabian; Vlasselaers, Dirk; Desmet, Lars; Lamote, Stoffel; Delrue, Heidi; Beckers, Marc; Casaer, Michaël P.; Wouters, Pieter; Van den Berghe, Greet; Meyfroidt, Geert
Abstract : Objectives: To assess whether near-infrared cerebral tissue oxygen saturation, measured with the FORESIGHT cerebral oximeter (CAS Medical Systems, Branford, CT) predicts PICU length of stay, duration of invasive mechanical ventilation, and mortality in critically ill children after pediatric cardiac surgery. Design: Single-center prospective, observational study. Setting: Twelve-bed PICU of a tertiary academic hospital. Patients: Critically ill children and infants with congenital heart disease, younger than 12 years old, admitted to the PICU between October 2012 and November 2015. Children were monitored with the FORESIGHT cerebral oximeter from PICU admission until they were weaned off mechanical ventilation. Clinicians were blinded to cerebral tissue oxygen saturation data. Interventions: None. Measurements and Main Results: Primary outcome was the predictive value of the first 24 hours of postoperative cerebral tissue oxygen saturation for duration of PICU stay (median [95% CI], 4 d [3–8 d]) and duration of mechanical ventilation (median [95% CI], 111.3 hr (69.3–190.4 hr]). We calculated predictors on the first 24 hours of cerebral tissue oxygen saturation monitoring. The association of each individual cerebral tissue oxygen saturation predictor and of a combination of predictors were assessed using univariable and multivariable bootstrap analyses, adjusting for age, weight, gender, Pediatric Index of Mortality 2, Risk Adjustment in Congenital Heart Surgery 1, cyanotic heart defect, and time prior to cerebral tissue oxygen saturation monitoring. The most important risk factors associated with worst outcomes were an increased SD of a smoothed cerebral tissue oxygen saturation signal and an elevated cerebral tissue oxygen saturation desaturation score. Conclusions: Increased SD of a smoothed cerebral tissue oxygen saturation signal and increased depth and duration of desaturation below the 50% saturation threshold were associated with longer PICU and hospital stays and with longer duration of mechanical ventilation after pediatric cardiac surgery. Abstract : Supplemental Digital Content is available in the text.